Synthesis of high strength ambient cured geopolymer composite by using low calcium fly ash - Khan, M.; Shaikh, Faiz; Hao, Yifei; Hao, Hong (Elsevier BV, 2016)
© 2016 Elsevier Ltd. Geopolymer is an environment-friendly binder, which has gained significant interest amongst the research community in last few decades. Previous studies show that low calcium fly ash geopolymer exhibits similar or comparatively better mechanical properties upon heat curing. This paper evaluates the viability of developing high strength geopolymer composite by using low calcium fly ash as a principal binder and its partial replacement with slag, hydrated lime and ultra-fine fly ash in the mortar mixtures. The solid precursors were activated with a multi-compound mixture of 12 M sodium hydroxide and D-grade sodium silicate at an alkaline liquid/binder ratio of 0.60 at ambient temperature. The effect of binder composition on the workability and compressive strength gain from 3 to 28 days is discussed. Mineralogical and microstructural properties were also observed to identify the different reaction phases, thermal decomposition, morphology and cumulative porosity of the resulting geopolymer formulations. The results indicated that the compressive strength of geopolymer binder is primarily dependent upon the nature of source materials for a selected alkali-activating solution. Ambient cured geopolymer composites with very high compressive strength, i.e. more than 100 MPa were obtained with adequate workability by including an optimum amount of slag in low calcium fly ash geopolymer. The results also reflected a dense microstructure and reduced porosity for fly ash-slag geopolymer composites. However, the addition of UFFA and hydrated lime at higher proportions was diminutively effective in the selected alkaline activator to binder or water to solids ratios.